Pneumomediastinum in COVID‐19 disease: Clinical review with emphasis on emergency management - Ezhilkugan Ganessane; Anandhi Devendiran; Swetha Ramesh; Amaravathi Uthayakumar; Vinodha Chandrasekar; Anuusha Subathra Sadasivam; Balamurugan Nathan; Manu Ayyan (Journal of the American College of Emergency Physicians Open, 2023)
Abstract Pneumomediastinum can be primary (spontaneous) or secondary to iatrogenic, traumatic, and non‐traumatic causes. The incidence of spontaneous and secondary pneumomediastinum is higher in patients with coronavirus disease 2019 (COVID‐19) compared to the general population. So, pneumomediastinum should be considered in the differential diagnosis of any patient with COVID‐19 presenting with chest pain and breathlessness. A high level of suspicion is required to diagnose this condition promptly. Unlike in other disease conditions, pneumomediastinum in COVID‐19 has a complicated course with higher mortality in intubated patients. No guidelines exist for managing pneumomediastinum patients with COVID‐19. Therefore, emergency physicians should be aware of the various treatment modalities besides conservative management for pneumomediastinum and life‐saving interventions for tension pneumomediastinum.